2019
DOI: 10.1080/17520843.2019.1596963
|View full text |Cite
|
Sign up to set email alerts
|

Inflation dynamics in Uganda: a quantile regression approach

Abstract: This paper considers the measurement of inflation persistence in Uganda and how this has changed over time. As the data does not follow a normal distribution, we make use of the quantile regression approach to investigate how various shocks may affect the rate of inflation within different quantiles. The measures of inflation include headline inflation, the current measure of core inflation, and an alternative measure of core inflation. The results suggest that while a unit root is found in many of the upper q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The researcher multiplied the time lost by Uganda’s minimum hourly wage of $0.15 per hour [ 28 ] to obtain the indirect cost. We valued patients’ and caregivers’ time using the minimum wage in Uganda as a proxy for the value of time for a person who is a non-wage earner[ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…The researcher multiplied the time lost by Uganda’s minimum hourly wage of $0.15 per hour [ 28 ] to obtain the indirect cost. We valued patients’ and caregivers’ time using the minimum wage in Uganda as a proxy for the value of time for a person who is a non-wage earner[ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the field of macroeconomic policy and management, the relationship between inflation and unemployment in Uganda is a topic of great interest and relevance. A country's economic well-being is directly impacted by two crucial macroeconomic indicators: unemployment, which is the percentage of the labor force that is actively looking for work but is unable to find it, and inflation, which is defined as the consistent increase in the general price level of goods and services over time (Anguyo, Gupta, & Kotzé, 2020). Understanding the dynamics between inflation and unemployment is essential for policymakers in Uganda to formulate effective monetary and fiscal policies that promote price stability, sustainable economic growth, and full employment.…”
Section: Inflation and Unemployment In Ugandamentioning
confidence: 99%
“…That is why academia, policy makers, and other concerned stakeholders conduct ex ante or ex post research to investigate theses structural changes in numerous financial and economic variables. Ruch et al (2020), Anguyo et al (2020), Hegerty (2020), Nath and Sarkar (2019), Gil-Alana (2019), Orlowski (2017) examine the break dates and the impact of structural changes on inflation series with regards to other variables. Ruch et al (2020) predict inflation variables using factor-augmented VARs (FAVAR), time-varying parameter vector autoregressive models (TVP-VARs), and structural break models.…”
Section: Literaturementioning
confidence: 99%
“…Their results also showed that structural break did not enhance the predictability of inflation. Anguyo et al (2020) examine structural changes and measurement of inflation persistence over time using the Uganda data. Using the regression quantile, they find higher levels of persistence after 2006 and during the inflation targeting period.…”
Section: Literaturementioning
confidence: 99%